NGOs in development perspective - Jain, R. B. (Ed.) (Delhi, 1995)
The essays in this volume seek to examine critically the place NGOs in public administration system and their emerging re in development process. While the study suggests that it is time to relinquish the idea of NGOs as competitors to public administration and focus attention on their capabilities as innovators in strengthening the service responsiveness of the state, at the same time it is necessary to reflect upon the innumerable constraints and controversies under which they operate. Conceptualising and assessing the impact of their operations as catalyst in grass-root development in the Third World, especially in the Indian context, the essays make a strong plea for a more cooperative government-NGO interface an objective framework of their autonomous operation and surveillance, evolution of a system of accountability, a cautionary institutional and administrative development conducive to the spirit of voluntarism, a multi- level, multi-pronged NGO networking for greater coordination, strength effectiveness, and an increased involvement with the decision-making process of national and international organisations and the UN system. These are some of the most crucial measures which need to be urgently taken if the objectives of a people-centred sustainable development and social transformation are to be achieved in the context of the trend towards a world market economy and the processes of globalisation.
Keywords: Non-governmental organisations-India